2020
DOI: 10.1093/ibd/izaa144
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Psychotherapy on Quality of Life in IBD Patients: A Systematic Review

Abstract: Background Patients with inflammatory bowel disease (IBD) express a need for additional psychotherapy; however, psychological support is not incorporated in the routine care of persons with IBD. This systematic review aims to assess the effect of psychotherapy on quality of life (QoL). Methods A systematic search was conducted on October 7, 2019, using Embase, Medline (Ovid), PubMed, Cochrane, Web of Science, PsycInfo, and Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 67 publications
(75 reference statements)
0
22
0
Order By: Relevance
“…At our center, psycho‐gastroenterological multimodal therapy was administered by a health psychologist trained in psycho‐gastroenterology practice, who was not involved in initial or follow‐up patient evaluations. This model has been utilized in other centers to provide cognitive and behavioral therapy, gut directed hypnotherapy, biofeedback, and diaphragmatic breathing to patients with DGBI, 5,6,20,21 and non‐DGBI gastrointestinal disorders such as inflammatory bowel disease 22,23 . Although related to psychotherapy for affective disorders, this psycho‐gastroenterology skill set is specifically adapted for management of individuals with DGBI and includes techniques to reduce hypervigilance, symptom‐related anxiety, autonomic nervous system arousal, and catastrophizing while improving coping and day‐to‐day function 20,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At our center, psycho‐gastroenterological multimodal therapy was administered by a health psychologist trained in psycho‐gastroenterology practice, who was not involved in initial or follow‐up patient evaluations. This model has been utilized in other centers to provide cognitive and behavioral therapy, gut directed hypnotherapy, biofeedback, and diaphragmatic breathing to patients with DGBI, 5,6,20,21 and non‐DGBI gastrointestinal disorders such as inflammatory bowel disease 22,23 . Although related to psychotherapy for affective disorders, this psycho‐gastroenterology skill set is specifically adapted for management of individuals with DGBI and includes techniques to reduce hypervigilance, symptom‐related anxiety, autonomic nervous system arousal, and catastrophizing while improving coping and day‐to‐day function 20,24 .…”
Section: Discussionmentioning
confidence: 99%
“…This model has been utilized in other centers to provide cognitive and behavioral therapy, gut directed hypnotherapy, biofeedback, and diaphragmatic breathing to patients with DGBI, 5,6,20,21 and non-DGBI gastrointestinal disorders such as inflammatory bowel disease. 22,23…”
Section: Discussionmentioning
confidence: 99%
“…In a 2019 literature review Paulides et al (2021) concluded that psychotherapy can improve the quality of life of IBD patients. They further stated that additional studies are needed to introduce psychological intervention immediately after diagnosis so that the patient learns good constructive coping strategies throughout life.…”
Section: Introductionmentioning
confidence: 99%
“…IBD affects interpersonal relationships, life activities, social participation, and mental well-being [ 8 , 9 , 10 ]. Psychological support does not belong to the standard care of patients with IBD although it is suggested that psychotherapeutic interventions can improve the quality of life of individuals with IBD [ 11 ]. Furthermore, IBD may compromise patients’ workability and impact other parameters of work impairment, such as absenteeism, presenteeism, activity, and productivity loss [ 12 ].…”
Section: Introductionmentioning
confidence: 99%